Marine forensics : a molecular tool for trade monitoring and compliance in southern African fisheries, with focus on commercially exploited elasmobranch species - Asbury, Tamaryn Anne (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.